COMBINATION OF MELODIC LINES, PERCUSSIVE ELEMENTS AND ACCOMPANIMENT FOR THE JAZZ DOUBLE BASS - SOCICAN, IGOR (Studiul Artelor şi Culturologie: Istorie, Teorie, Practică, 2021)
The present article is dedicated to the combination of different methods of interpretation on the double bass in jazz music, while providing as much information and resources as possible for the further development and study of different melodic, percussive and accompaniment styles of the jazz double bass. Namely, it is proposed to examine different percussion techniques on the double bass and their notation versions .This problem is examined for the first time in the national music science